An empirical analysis of economic exposure and its determinants of the miscellaneous companies in Indonesia - M. Shabri Abd. Majid; Zaida Rizqi Zainul; A. Syakir Jalil (Proceedings of AICS - Social Sciences, 2013)
This research empirically measures the economic exposure of 11 selected miscellaneous companies in Indonesia. It also attempts to empirically explore the influence of firm size (SIZE) export (EXPORT), liquidity (QR), and leverage (LTD) on the economic exposure of those companies. Annual data from 2007 to 2010 which was collected from the www.idx.co.id and www.bi.go.idwere used and analyzed by the multiple linear regression to measure the economic exposure and examine the influences of SIZE, EXPORT, QR, and LTD on the economic exposure. Both partial (t-test) and simultaneous (F-test) hypotheses were constructed and tested at the 5% level of significance. Data was analyzed by the software of SPSS for Windows. The research documented that, with the exception of the QR which has a negative and significant effect partially on the economic exposure, all other variables, i.e., SIZE, EXPORT, and LTD were found to have insignificant effects. Meanwhile, based on the F-test, the research found that the SIZE, EXPORT, QR, and LTD affected simultaneously and significantly the economic exposure of the companies. These findings imply that in order to manage their economic exposure, the companies should control these variables, especially QR.Keywords :Economic Exposure; Firm Size; Export Ratio; Quick Ratio; Long Term Debt to Total Asset Ratio; Miscellaneous Companies; Indonesia.